Adrenal gland injury due to gunshot - Vivek Angara; Jody C. Digiacomo (Chinese Journal of Traumatology, 2020)
Adrenal gland trauma is a rare phenomenon, due to the small size and retroperitoneal location of the organ. The majority of adrenal gland trauma is due to blunt force injury and is only rarely encountered due to the penetrating mechanisms. A 20-year-old male sustained a gunshot wound to the left abdomen. Upon exploration, he was found to have a through and through injury to the left adrenal gland, among other injuries. Injury to the adrenal gland due to penetrating trauma is exceptionally rare. The principles of management are to control bleeding from the gland with debridement and hemostasis rather than attempt to resect the entire organ. The management of a penetrating injury to the adrenal gland is straightforward and should not be a contributor to a patient's morbidity or mortality.